Evaluasi Ekonomi dari Produksi Nanopartikel Magnesium Oksida melalui Metode sol-gel Combustion - Dea Bella Dewary Atika Putri; Asep Bayu Nandiyanto (STRING (Satuan Tulisan Riset dan Inovasi Teknologi), 2019)
The purpose of this study is to determine the feasibility of the project to make Magnesium Oxide (MgO) sol gel combustion method by evaluating the engineering and economic aspects. Several economic evaluation parameters are analyzed to inform the potential production of MgO nanoparticles, the length of time required for an investment to recover the total initial expenditure (PBP), project conditions for a production in the form of a production function in years (CNPV), project profits and others. The results showed that the production of MgO nanoparticles was very prospective. Technical analysis to produce 1.38 kg of MgO nanoparticles per day shows the total cost of the equipment purchased was USD 91,542.86. PBP analysis shows that investment profitable after more than 3 years. This project can compete with PBP capital market standards because the investment will return in a short time. To ensure the feasibility of the project, the project is estimated from the ideal conditions to the worst cases in production, including labor, sales, raw materials, utilities, and external conditions (e.g. tax).